Risk behaviour of women, livelihood activities and household food insecurity: evidence from Ghana - Ayifah, Emmanuel (My University, 2017)
Women’s risk behaviour and how it affects their choice of livelihood activities and household food insecurity has been least explored empirically. Using experimental risk behaviour data matched with socioeconomic characteristics and food insecurity data collected from 1320 women and their households in the Yilo and Lower Manya Krobo districts of the Eastern region of Ghana, I investigated this issue by focusing on three core research questions: (1) What is the effect of religion on risk behaviour of women? (2) What is the relationship between risk behaviour and livelihood activities of women? And (3) Does risk behaviour of women matter in household food insecurity and food insecurity coping strategies? This thesis is divided into three core papers, with each paper focusing on a specific research question. Religious doctrines may guide individual attitudes and preferences, including risk behaviour among others. The first paper examines the effect of religion on the willingness to take risk amongst 1,209 rural women. The study found that whereas religious affiliation influences the decision to engage in risk, it does not in any way influence the level of risk-taking thereafter. In particular, the study established that relative to the non-religious, religious affiliation of a woman influences her willingness to engage in risk negatively. However, there is very little difference in such willingness to engage in risk between the different religious groups (Pentecostals, Protestants, Catholics, Muslims and Traditional). Risk attitudes are fundamental in explaining choices that individuals make in any domain that involves uncertainty around a future outcome. Based on the literature, it is apparent that no study has established a causal relationship between risk preferences and choice of livelihood for any African country, and certainly not for Ghana. Furthermore, globally, no study has focused on women specifically, and certainly not in the rural African context. Hence, the second paper investigated the relationship between risk behaviour and livelihood activities. A theoretical model is developed - this indicated that a risk averse woman would engage in a livelihood activity with very little risk such as paid employment, while a risk-seeking woman would engage in a livelihood activity involving high risk, such as farming. The model is tested empirically, and in order to deal with any potential endogeneity, instrumental variables regression was used, with religion as an instrument for risk preference to isolate the causal effect of risk behaviour of women on their choice of livelihood activity. The paper found that women who are willing to take risk are more likely to be farmers, rather than to be unemployed (have no livelihood activity). Also, risk-seeking women were indifferent between having a vocation or being involved in petty retailing and being unemployed. In addition, risk-seeking women were less likely to be in paid employment than to be unemployed. Despite the substantial evidence on women’s role in food security, there is a paucity of studies explicitly looking at the effect of women’s risk behaviour on food insecurity. Therefore, the third and last paper addressed the question whether or not risk behaviour of women matters in household food insecurity. This study contributed to filling the gap in the literature by using a panel data to examine the effect of risk behaviour on household food insecurity and coping strategies. A theoretical model is developed where risk attitudes and food insecurity are connected through precautionary savings. The model indicates that the more risk averse a woman is, the greater the level of precautionary savings, and hence, the lower the household food insecurity. The paper is twofold: the first part estimates the effect of risk behaviour of women on household food insecurity, and the second looks at the effect of risk behaviour on the coping strategies households adopt during food insecurity episodes. The study shows that risk-seeking behaviour of women increases household food insecurity. Also, risk-loving women not only have to adopt more coping strategies, but also more drastic coping strategies, all things being equal. The results presented in this thesis have implications for policy. Policy design and implementation process needs to take cognizance of the risk behaviour of women as it may affect women’s economic behaviour and policy outcomes. Additionally, the religious background of women should be taken into consideration as risk behaviour is found to be influenced by religion. Likewise, policy interventions aimed at enhancing livelihood activities of women should also take into consideration individual risk behaviour. However, livelihood enhancing policies or programmes should be context specific, because different livelihood activities are influenced by risk behaviour differently. Lastly, given that risk behaviour of women influences household food insecurity, as well as some of the strategies households adopt to cope with food insecurity episodes, policies and programmes aimed at improving access to food, should take into consideration women’s risk behaviour.
A thesis submitted to the School of Economic & Business Sciences, Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy in Economics, University of the Witwatersrand, Johannesburg, 2017
Keywords: Food security--Economic aspects; Food security--Ghana; Women and the environment--Ghana